Analisis Kepemimpinan Perempuan dalam Pemerintahan Desa (Studi Kasus di Desa Lamea, Kecamatan Wewiku, Kabupaten Malaka Tahun 2013) - Clotilde Seran; Antonius Bere (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
Women in the village government in Wewiku District, Malaka Regency in 2013, the number of Lamea Village officials is more dominant than Seserai, Lorotolus and Alkani villages. Therefore, the main problem raised in this study is to find out why the number of women in the Lamea Village government structure is more dominant than other villages and how the leadership patterns of female village heads and village officials are in organizing village government in Lamea Village, Wewiku District. The method used in this study is a qualitative description using a descriptive case study method. The results of the study indicate that the reason for the dominance of women in the government structure in Lamea Village is because female leaders have high intelligence, have a vision and mission and are able to communicate the vision and mission well, and have high communication skills. In addition, the myth that women are not able to lead, therefore it is necessary to empower women, fight for gender equality, a balanced division of roles and functions between men and women, feel more comfortable and compatible with women. While in the pattern of female leadership, not everything is running optimally. Other findings from this study are: the concept of listening from ema tetun is hanono, rona malu, loke tilun no neon laran hodi rona sasa maak ema dale mai ita. The approaches used are hamata, kalalan and mon metan. The concept of empathy according to ema tetun is nu'u dar, nu'u kmesak, hanesan, manesak which means feeling the same fate and suffering. The approaches used are haklaran malu, hanoin malu, hadomi malu, sudi hamutu. The concept of the ability to serve according to ema tetun is haliku. The approaches used are tu'an malu, tulun malu, hakneter haktaek. The symbols used are tanasak, kabir, tais feto and tais mane. The concept of commitment to human growth according to ema tetun is neon metin. The approaches used are meno malu and hala'ok. The concept of building humans according to ema tetun is hader renu, foti renu. The approaches used are karian hamutu and hakawak